MEMBANGUN BUDAYA TOLERANSI DAN PERDAMAIAN MELALUI PENDIDIKAN DI INDONESIA - Aminulloh, Ali; Ali Al Azhar, Muhammad; Ulya safitri, Naffisa; Nurjanah (LP2M Universitas Muslim Nusantara Al Washliyah, 2024)
Building a culture of tolerance and peace in Indonesia is very important because this country has rich ethnic, religious, cultural and social diversity. To make this happen, it can be done through education. This article aims to find out how to build a culture of tolerance and peace through education in Indonesia. This research is literature study research, namely an in-depth research method for investigating and analyzing relevant literature in a particular field of knowledge or topic. This paper explains that a culture of tolerance and peace can be achieved by including educational material about tolerance and peace in the school curriculum and providing a learning environment that supports open discussion about differences. Apart from that, involving educators and teaching staff in training on the importance of understanding and respecting diversity is also an integral part of building a culture of tolerance and peace.